Neonatal lupus erythematosus complicated by improved congenital complete heart block. Issue 4 (5th August 2013) - Isayama, Tetsuya; Inamura, Noboru; Shiono, Nobuko; Kitajima, Hiroyuki
Abstract: Complete congenital heart block (CCHB) accompanied with neonatal lupus erythematosus is caused by an immune reaction between maternal anti‐Ro/SSA antibodies and the fetal heart and is generally considered an irreversible process. This reaction mostly occurs before 30 weeks' gestation, especially between the 20th and 24th week. Reported here is an atypical case of neonatal lupus erythematosus with CCHB detected after 32 weeks' gestation that showed postnatal improvement in the degree of heart block after preterm delivery and immunoglobulin use. The clinical condition of the infant worsened with an increase in heart rate due to possible cardiomyopathy induced by the immune reaction.